BAS/BSCR47 Quantitative metabolic profiling of subclinical atherosclerosis by serum NMR metabonomics. Issue 17 (26th August 2010) - Würtz, P; Soininen, P; Kangas, A J; Magnussen, C G; Raiko, J H; Mäkinen, V P; Groop, P H; Thomson, R; Savolainen, M J; Juonala, M; Viikari, J; Kähänen, M; et al.
Abstract : Objective: To determine associations of systemic metabolites with subclinical atherosclerosis. Methods: 4407 serum samples were measured by nuclear magnetic resonance (NMR) spectroscopy from the Cardiovascular Risk in Young Finns Study, and carotid intima-media thickness (IMT) was assessed by ultrasound. Numerous lipoprotein lipids subclasses as well as low-molecular-weight metabolites were quantified from the NMR data. Results: In these young adults (aged 24–45 years) data-driven analysis using self-organising maps showed distinct metabolic phenotypes associated with elevated IMT. The phenotypes were characterised by varying combinations of metabolic disturbances including elevated very-low-density lipoprotin (VLDL) and LDL subclasses, but also several low-molecular-weight metabolites. Results for 6-year incidence of high carotid IMT and IMT progression as shown by discrimination and reclassification will also be discussed. Conclusion: The study showed different metabolic phenotypes inherently associated with subclinical atherosclerosis. Prediction of subclinical atherosclerosis was improved by comprehensive metabolic profiling. The findings substantiate developments towards the use of multi-metabolic risk phenotypes in cardiovascular risk assessment.